2019
DOI: 10.1111/jog.14032
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal menstruation after radical trachelectomy and its effects on fertility

Abstract: Aim: To evaluate and identify the risk factors for abnormal menstruation after radical trachelectomy. Methods: This study included 58 patients who underwent radical trachelectomy at our hospital between April 2005 and January 2018. Patients were divided into groups of those with no change in postoperative menstruation (regular [R] group; n = 46) and those with abnormal menstruation such as amenorrhea or hypomenorrhea (irregular [I] group; n = 12). The perioperative characteristics and fertility of the groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This may often lead to development of residual cervical necrosis [6]. The residual cervical cavity may thus become narrowed, often leading to abnormal menstruation in patients following RT [7]. In cases with early miscarriage with no history of RT, dilatation and curettage (D&C) is usually performed [8].…”
Section: Counseling About Perinatal Management Before Pregnancymentioning
confidence: 99%
“…This may often lead to development of residual cervical necrosis [6]. The residual cervical cavity may thus become narrowed, often leading to abnormal menstruation in patients following RT [7]. In cases with early miscarriage with no history of RT, dilatation and curettage (D&C) is usually performed [8].…”
Section: Counseling About Perinatal Management Before Pregnancymentioning
confidence: 99%
“…However, women who undergo RT also have simultaneous cervical cerclage to prevent future preterm delivery, and residual cervical necrosis occurs in an average of 10.5% of cases 3 . Therefore, the residual uterine cavity is often narrowed after RT, and some patients also suffer from abnormal menstruation 4 . Although dilatation and curettage (D&C) has been performed for early‐pregnancy miscarriage after RT, 5 there is concern about damaging the cervical cerclage or the possibility of developing endometritis.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, the residual uterine cavity is often narrowed after RT, and some patients also suffer from abnormal menstruation. 4 Although dilatation and curettage (D&C) has been performed for early-pregnancy miscarriage after RT, 5 there is concern about damaging the cervical cerclage or the possibility of developing endometritis. Bernardini et al reported that three out of three RT patients with early miscarriage did not need D&C. 5 Moreover, Plante et al reported that among eight patients with early miscarriage, five patients did not need D&C, one needed misoprostol and D&C, and one was treated using misoprostol alone; since one other patient did not abort spontaneously using misoprostol and developed endometritis and placental tissue retention, she needed to undergo D&C and take antibiotics.…”
mentioning
confidence: 99%